2012
DOI: 10.1186/1746-6148-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of feline leukaemia virus and feline immunodeficiency virus in peninsular Malaysia

Abstract: BackgroundFeline leukaemia virus (FeLV) and feline immunodeficiency virus (FIV) are major causes of morbidity and mortality in domestic and wild felids. Despite the clinical importance of feline retroviruses and the growing interest in cats as pets, information about FeLV and FIV in Malaysia is presently insufficient to properly advise veterinarians and pet owners. A cross-sectional study was carried out from January 2010 to December 2010 to determine the prevalence and risk factors associated with FeLV and FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
80
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(124 citation statements)
references
References 27 publications
17
80
7
2
Order By: Relevance
“…This information is crucial for control of FeLV infection in domestic cats as there is currently no data on its prevalence in Zimbabwe. The FeLV p27 antigen in blood samples in this study (41%) is higher than those from both developing (Bande et al 2012;De Almeida et al 2012) and developed (Bandecchi et al 2006;Gabor et al 2001;Lee et al 2002;Little et al 2009) countries in other regions where moderate (10% -20%) to low (< 10%) prevalences have been reported. The observed data may be influenced to an extent by test parameters, a small sample size and sampling bias -as cats presented to veterinary clinics only may not be representative of other apparently healthy cats that did not visit the clinics.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This information is crucial for control of FeLV infection in domestic cats as there is currently no data on its prevalence in Zimbabwe. The FeLV p27 antigen in blood samples in this study (41%) is higher than those from both developing (Bande et al 2012;De Almeida et al 2012) and developed (Bandecchi et al 2006;Gabor et al 2001;Lee et al 2002;Little et al 2009) countries in other regions where moderate (10% -20%) to low (< 10%) prevalences have been reported. The observed data may be influenced to an extent by test parameters, a small sample size and sampling bias -as cats presented to veterinary clinics only may not be representative of other apparently healthy cats that did not visit the clinics.…”
Section: Discussioncontrasting
confidence: 64%
“…The factors that predispose cats to FeLV infection include young age, intact male cats, having access to outdoor life and living in multicat houses (Bande et al 2012). Although evidence of FeLV infection in domestic cats (Felis domesticus) has been documented in many regions of the world, there is a lack of information about its prevalence in most parts of Africa, except for reports from Nigeria and South Africa (Bobade, Nash & Rogerson 1988;Schoeman et al 2001;Schoeman et al 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The distribution of animals infected with these retroviruses varies considerably depending on the geographic region, the feline population evaluated, and the diagnostic method chosen (Luria et al, 2004;Levy et al, 2008;Gleich et al, 2009). This explains the variations of seroprevalence from 2.5 to 31.3% for FIV and from 2.3 to 30.4% for FeLV that have been found in studies from different parts of the world (Arjona et al, 2000;Levy et al, 2006;Bande et al, 2012). In Brazil, the seroprevalence ranges from 5.6 to 16.7% for FIV and from 0.33 to 32.5% for FeLV (Teixeira et al, 2007;Macieira et al, 2008;Sobrinho et al, 2011) and, additionally, the infection rates found using molecular tests have ranged from 2 to 15.7% for FIV and from 0.5 to 47.5% for FeLV (Coelho et al, 2011;Marçola, 2011;Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…FIV prevalence varies by geographic region with the incidence in North America reported at 2.5 % (2006), 5.4 % in Bangkok, Thailand (2014), 9.5 % in Ankara, Turkey (2013), 23.2 % in Japan (2008) and 31.1 % in peninsular Malaysia (2012), equating to millions of FIVinfected animals worldwide [1][2][3][4][5].…”
Section: Feline Immunodeficiency Virus (Fiv) Is a Lentivirus That Shamentioning
confidence: 99%